DATABASE HEALTH MONITORING (DHM) SEBAGAI ALAT MONITORING KESEHATAN DATABASE - Ary Budi Warsito; Muhamad Yusup; Rivai Sungkowo (CCIT Journal, 2016)
DSS (Decision Support Systems) has the notion that a computer-based system that presents and process information that allows decisions to be more productive, dynamic and innovative [1]. In this study, a concept with the name DHM (Database Health Monitoring). DHM concept is a form of development of the DSS is a concept of how to analyze the health of a database in which the level of health in the database is measured by the number of empty fields. To calculate the number of empty fields required sql queries which query results are then processed into a protocol JSON (JavaScript Object Notation) is a concise format computer data exchange [6]. In JSON protocol is what ultimately made a dashboard. The results are displayed in the form of dashboards to facilitate leadership read the information received. In addition, the leadership does not need direct access to the database to get information.